(untitled) (Research, Society and Development, 2020)
This study analyzes the value proposition of an airport hub under the theoretical lens of business models. It aims to identify and verify the contribution of airport hubs to the most economical route operations for aviation companies. The methodological procedures adopted in this analysis include bibliographic research and empirical research, through interviews with aviation professionals to obtain information that reflects the reality at hub airports. The analysis can be justified in the search for effective factors to generate value and create competitive advantages for aviation companies. The strategy and business model confirm its usefulness in carrying out processes related to Hub airports.